Lipoma Arborescens of the Knee: Case Report - Sibel Özbudak Demir,; Sibel Kibar,; Meltem Aras,; Füsun Köseoğlu, (Archives of Rheumatology, 2007)
Lipoma arborescens is a rare intra-articular lesion with unknown etiology. It is characterised by villous lipomatous proliferation of the sinovium and typically located in the knee. Gradual joint swelling, variable pain, intermittent effusion and a range of motion limitation are the symptoms that can be seen during the course of lipoma arborescens. It is important to make early diagnosis using magnetic resonance imaging. This diagnosis should be considered in the differential diagnosis of patients with chronic joint effusion. In this article, a case presenting unilateral knee swelling, limitation of range of motion and diagnosed lipoma arborescens by magnetic resonance imaging is reported. (Rheumatism 2007; 22: 147-50)